(untitled) (El Hilo de la Fabula, 2024)
Yourcenar’s relationship with travel is obvious in the itinerary of her life, which has been meticulously reconstructed in recent biographies, and in her abundant correspondence, which was discovered posthumously, in which she discusses in detail her travel plans, her successive experiences and the lessons she draws from them. It is interesting to highlight an original concept of travel in Yourcenar that combines with her philosophy of life and to relate it to some of her works, which gives us one of the keys to her complex personality and her main characters. And to complement it with my own experience of travel.